Family Support for Short-Status Pregnant Women to Prevent Gestational Stunting : Phenomenological Studies - Zuriati Muhamad; St. Surya Indah Nurdin; Asnidar Asnidar; Ilyas Abbas Ilyas Abbas; Dwi Nur Octaviani Katili (Journal of Public Health and Pharmacy)
Introduction: Maternal short stature with a height < 150 cm are at risk of giving birth to short babies (body length < 48 cm) Then, so that they become small and small children. The purpose of this study was to analyze family support for short pregnant women in dealing with their pregnancies.